The leadership qualities formation of future educators by means of student self-government - Gurevich, Roman; Brovchak, Liudmyla; Kholkovska, Iryna (Національний технічний університет "Харківський політехнічний інститут", 2019)
The article reveals the meaning of the notion “leadership”. Modern national and foreign approaches which determine leadership have been analyzed. Processes of leader-ship and management have been compared. Main characteristics of future educators` leader-ship qualities have been proposed. Components in the structure of leadership qualities of stu-dents of higher educational establishments have been suggested: the self-organization ability, the organizational activity ability, the interpersonal cooperation organization ability. Criteria of future educators `leadership qualities maturity have been determined: cognitive, opera-tional, personal. The emphasis is placed on the fact, that educational establishments have the opportunity to form leadership qualities with the help of the students` participation in the work of self-governing bodies. The brief description of the experimental approach of students` who are going to be future educators, leadership qualities by means of student self-govern-ance has been suggested. The educational potential of “Young Leader School” (translitera-tion “Shkola Molodoho Lidera”) in the formation of pedagogical university students` leader-ship qualities has been viewed. The staged nature of the organization of various forms of the extracurricular educational activities of students has been revealed.

У статті розкривається зміст поняття "лідерство". Проаналізовано сучасні національні та зарубіжні підходи, які визначають лідерство. Порівняно процеси лідерства та управління. Запропоновано основні характеристики лідерських якостей майбутніх вихователів. Запропоновано компоненти в структурі лідерських якостей студентів вищих навчальних закладів: здатність до самоорганізації, здатність до організаційної діяльності, здатність організації міжособистісної співпраці. Визначено критерії зрілості лідерських якостей майбутніх вихователів: пізнавальна, оперативна, особистісна. Акцент робиться на тому, що навчальні заклади мають можливість формувати лідерські якості за допомогою участі студентів у роботі органів самоврядування. Запропоновано короткий опис експериментального підходу студентів, які будуть майбутніми педагогами, лідерськими якостями за допомогою студентського самоврядування. Розглянуто освітній потенціал "Молодої школи лідерів" (транслітерація "Школа молодого лідера") у формуванні лідерських якостей педагогічних студентів університету. Виявлено поетапний характер організації різноманітних форм позашкільної виховної діяльності студентів.
Формування якості лідерства майбутніх освітелів засобами студентського самоврядування
Keywords: leadership; leadership theories; leadership conceptions; leadership quali-ties; students; student self-governance; future teachers; лідерство; теорії лідерства; концепція лідерства; лідерські якості; студенти; студентське самоврядування; майбутні вчителі